Kebutuhan Gizi Ibu Hamil Pada Masa Pandemi Covid-19 - Novita Nining Anggraini; Riris Dwi Anjani (Universitas Muhammadiyah Semarang, 2021)
Nutritional needs of pregnant women are important factors, both for the fulfillment of nutrition of pregnant women and the growth and development of fetuses in the womb. Mothers must have good nutritional status and consume a variety of foods both in proportion and in number. During the Covid-19 pandemic, a balanced nutrition mix is required. Pregnant women consume foods with balanced nutrition can boost the immune system, and lower the risk of chronic diseases and infectious diseases. The purpose of this study is to find out the nutritional needs of pregnant women during the Covid-19 pandemic. The method used is a literature review study on the nutritional needs of pregnant women during the Covid-19 pandemic, literature sources using various journals from the google scholar database. Found 3 related journals consisting of national journals. The results obtained that the nutritional needs of pregnant women during the pandemic should be improved more than normal conditions because the mother must maintain the body's immunity condition well.